New Surface Properties in Porcelain Gres Tiles with a Look to Human and Environmental Safety. (2nd September 2012) - Bianchi, C. L.; Pirola, C.; Gatto, S.; Nucci, S.; Minguzzi, A.; Cerrato, G.; Biella, S.; Capucci, V.
Abstract : Traditional photocatalysis is here brought forward for both the use of nanosized TiO2 crystallites and the possibility to have a release of TiO2 particles during the final use of the manufactured products. In the present paper both the preparation and characterization of a new generation of photocatalytic tiles are presented. The originality of these products is the surface presence of microsized TiO2 as it is not clear yet the impact of the nanoparticles on both human and environmental safety. TiO2 is here mixed with a silica compound and the final thermal treatment at 680°C allows the complete surface vitrification which, in turn, makes the tiles surface strongly resistant to abrasion. Photocatalytic efficiency towards the degradation of NO x in gas phase was measured in both a batch and a plug-flow reactor. The latter reactor configuration was also modeled by digital simulations.